Multiple scattering theory for spectroscopies : a guide to multiple scattering computer codes – dedicated to C. R. Natoli on the occasion of his 75th birthday /: a guide to multiple scattering computer codes – dedicated to C. R. Natoli on the occasion of his 75th birthday. (2018) - Unknown
No abstract available